Disordered eating behaviors and associated factors among secondary school adolescents in Harar town, eastern Ethiopia: cross-sectional study - Tekola, Abainash; Regassa, Lemma Demissie; Berhanu, Hiwot; Mandefro, Miheret; Shawel, Samrawit; Kassa, Obsan; Roba, Kedir Teji (Frontiers in Psychiatry, 2024)
BackgroundAdolescent eating disorders impair physical and mental development and are associated with poor health outcomes in adulthood. However, there is little research on disordered eating in Ethiopia, particularly in the study area. As a result, the purpose of this study is to examine disordered eating behaviors and associated factors in secondary school adolescents in the study area.MethodsA school-based cross-sectional study was conducted among 1104 secondary school adolescents in Harar town from June 30 to July 15, 2022. Multistage cluster sampling was used, and data was collected using self-administered questionnaires. The eating attitude test-26 was used to assess disordered eating behaviors, and scores of 20 and above were considered to have disordered eating behaviors. A binary logistic regression analysis was done to identify factors associated with disordered eating behaviors and the statistical significance level was set at a p-value of 0.05.ResultIn this study, 28.37% [95% CI (25.73%, 31.16%)] of the adolescents had disordered eating behaviors. Being female [AOR = 1.81, 95% CI (1.29, 2.53)], being from a mother, attending technical school [AOR = 3.61, 95% CI: (1.85, 7.04)], and having a higher-educated father [AOR = 1.55, 95% CI: (1.02, 2.36)] were significantly associated with disordered eating behaviors. Furthermore, desire to lose weight [AOR = 2.09, 95% CI (1.49, 2.93)], smoking [AOR = 3.64, 95% CI (2.24, 5.91)], emotional problems [AOR = 1.7, 95% CI (1.14, 2.55)], and body image dissatisfaction [AOR = 0.96, 95% CI (0.94, 0.97)] were associated with disordered eating.ConclusionIn Harar, almost three out of ten secondary school adolescents had disordered eating behaviors. Personal, behavioral, and socio-demographic factors were associated with disordered eating. Since the prevalence of disordered eating is significant at the study site, all relevant stakeholders should have to develop appropriate interventions that target modifiable factors to reduce the burden.